Crown of thunder - Onyebuchi, Tochi (Razorbill, 2018)
Queen Karima's evil reign has many fleeing for safety to refugee camps. As Taj heads west with Aliya, they encounter sinister beasts that challenge Taj's own magical abilities. Along the way, both uncover brutal truths about their fates that leave them uncertain about their futures.